Assessment of Area Energy Efficiency of LTE Macro Base Stations in Different Environments - Shahab, Suhail Najm; Abdulkafi, Ayad Atiyah; Ayib Rosdi, Zainun (National Institute of Telecommunications, 2015)
Energy efficiency (EE) of wireless telecommunications has become a new challenge for the research community, governments and industries in order to reduce CO2 emission and operational costs. EE of base stations (BSs) in cellular networks is a growing concern for cellular operators to not only maintain profitability, but also to reduce the overall negative impact to the environment and economic issues for wireless network operators. In this paper, a framework focuses on the Area Energy Efficiency (AEE) evaluation of LTE BSs is presented. The parameters affect on the AEE and the coverage area of LTE BS in different scenarios are investigated. AEE analysis has been done using a few key performance indicators including transmit power, bandwidth, load factor with the assumption of different scenarios (urban, suburban and rural). The simulation results show that the LTE BSs have better AEE in an urban environment for cell radius less than 750 m compare with the suburban and rural environments. Furthermore, it is obvious that there is a strong influence of traffic load, BW and transmission power on AEE of LTE network. On the other hand, AEE increases significantly as the BW size increases. Finally, it has been shown that the AEE of LTE macro BS decreases with increasing the percentage of traffic load for all scenarios